UPAYA PENGEMBANGAN PRODUK UNTUK EFEKTIVITAS UMKM WAJIK IBU OOT DI DESA CIMANDE - Yulianingsih Yulianingsih; Dede Hamdani; Angga Permana Setiawan; Azwina Putri Anggari; Azizah Syafira Putri; Muhammad Ramadhan Al – Ues; Muhamad Hilman Albajuri; Muhamad As Ari; Vicky Amelia; Galuh Reza Dwi Agusta; Aldi Suherlan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Efforts to increase sales productivity and effectiveness for UMKM in Cimande Village through attractive product packaging and marketing innovations. The development of this innovation aims to make business actors, especially in Cimande Village, get maximum results from selling or the production process of their business. Especially in the current modernization era, it will greatly help them in making sales online, be it on the Marketplace or Social Media. Besides that with the existence of attractive product packaging than before, it will make it easier for consumers to get to know the type of UMKM product.